Experiences with organizing irrigators associations: a case study from the Magat River Irrigation Project in the Philippines - Bautista, H.B. (International Irrigation Management Institute, 1987)
The National Irrigation Administration has become well known in recent years for its innovative experimental programs for promoting farmer participation through strong farmer organizations. IIMI's first case study documents the experience of an irrigation management official, the author of this report, in an effort to organize irrigators associations (IAs) on the nearly half of the Magat River Multi-purpose Project area in a few short years. Most of these are now effective and active organizations. This experience is a valuable source of lessons and ideas for agency officials concerned with developing water-user associations on other systems.